KONSTRUKSI IDENTITAS KARAKTER LANSIA DALAM PENYUTRADARAAN FILM PENDEK “SEPI DI UJUNG HARI” - Jasmine, Raniya; Putra, I Made Denny Chrisna; Bumiarta, Made Rai Budaya (CALACCITRA: JURNAL FILM DAN TELEVISI, 2025)
This research explores the construction of elderly character identities in the short film "Sepi di Ujung Hari." Using Carl Plantinga’s theory, the study examines how cinematographic techniques, storytelling, and direction shape audience perception. Through script analysis, cinematography review, and directorial study, findings reveal that close-up shots, lighting contrast, and framing effectively convey emotions and psychological depth. The narrative structure further strengthens audience empathy by depicting the internal struggles of elderly individuals. Additionally, directorial choices, such as actor direction and blocking, significantly enhance authenticity. This study provides valuable insights for filmmakers in constructing engaging elderly characters and contributes to broader discussions on elderly representation in cinema.